Cases and materials on contracts - Milner, J. B. (James Bryce), 1918-1969 (Heritage., 1963)
This collection consists of extensively reproduced reports of law suits, some less extensive excerpts, and some excerpts that can best be described as notes of reports. The word ""materials"" covers these lesser excerpts, but it also covers a variety of other "legal" things.